Mechanized Tree Planting in Sweden and Finland: Current State and Key Factors for Future Growth - Back Tomas Ersson; Tiina Laine; Timo Saksa (Forests, 2018)
In Fennoscandia, mechanized tree planting is time-efficient and produces high-quality regeneration. However, because of low cost-efficiency, the mechanization of Fennoscandian tree planting has been struggling. To determine key factors for its future growth, we compared the operational, planning, logistical, and organizational characteristics of mechanized planting in Sweden and Finland. Through interviews with planting machine contractors and client company foresters, we establish that mechanized tree planting in Sweden and Finland presently shares more similarities than differences. Some notable differences include typically longer planting seasons in Sweden, and a tendency towards two-shift operation and less frequent worksite pre-inspection by contractors in Finland. Because of similar challenges, mechanized planting in both countries can improve cost-efficiency through education of involved foresters, flexible information systems, efficient seedling logistics, and continued technical development of planting machines. By striving to have multiple client companies, contractors can reduce their operating radii and increase their machine utilization rates. Above all, our results provide international readers with unprecedented detailed and comprehensive figures and characteristics of Swedish and Finnish mechanized tree-planting activities. We conclude that cooperation between Sweden’s and Finland’s forest industries and research institutes could enhance the mechanization level of Fennoscandian tree planting.